From Audience to Co-Creator: Participatory Public Program Design Around Fotografiska Shanghai’s The Pet Show - Pinyi Zhu (Art and Society, 2026)
Public programs have become an important means through which cultural institutions extend exhibition experiences beyond passive viewing. Yet in practice, “participation” is often treated as a general indicator of audience engagement, with insufficient distinction between the forms of interpretive agency that participants actually acquire. Taking Fotografiska Shanghai’s The Pet Show as an existing exhibition context, this article analyzes three proposed public programs conceived and designed by the author around the exhibition. Using a design-oriented curatorial case-study approach, it examines how structural design can create conditions for audiences to move from spectators to co-creators of cultural meaning, while comparing participatory mechanisms developed for different publics. Theoretically, the article brings together Nina Simon’s participatory museum model, Claire Bishop’s critique of participatory art, and Suzanne Lacy’s account of socially engaged practice. It proposes three modes of co-creation—material, narrative, and discursive—and identifies emotional perception, creative expression, and critical reflection as three parallel entry points into participation. The article argues that the analysis of participatory curating should focus not on the number of activities offered, but on how interpretive agency is redistributed and how participant-generated content enters processes of production, negotiation, and circulation. Because the three public programs remain curatorial design proposals rather than official programs implemented by Fotografiska Shanghai, the article limits its claims to the participatory possibilities supported by the designs and does not present anticipated effects as observed audience change. The framework is intended as an analytical and design tool that can be tested through subsequent practice and empirical research.